Plasma Atomic Layer Etching of SiO2 and Si3N4 with Low Global Warming C4H3F7O Isomers - Kim, Yongjae; Kang, Hojin; Kim, Changkoo; Chae, Heeyeop (ACS Sustainable Chemistry and Engineering, 2023)
In this study, plasma atomic layer etching (ALE) of C4H3F7O isomers heptafluoropropyl methyl ether (HFE-347mcc3), heptafluoroisopropyl methyl ether (HFE-347mmy), and perfluoro propyl carbinol (PPC) having low global warming potential were investigated and developed for SiO2 and Si3N4 films. Fluorocarbons generated from C4H3F7O isomer plasmas were used to fluorinate the SiO2 and Si3N4 surfaces, and the fluorinated surface was etched using Ar plasmas in the following step. The HFE-347mmy produces the lowest F 1s/C 1s ratio or carbon-rich fluorocarbon. The chemical sputtering threshold energy of Si3N4 was found to be 5-10 V lower than that of SiO2. The ALE window was observed in the range of 50-60 V for all isomers, and the EPC of SiO2 was determined to be 2.1, 1.8, and 5.2 Å/cycle for HFE-347mcc3, HFE-347mmy, and PPC, respectively. The EPC of Si3N4 is higher than that of SiO2 in all precursors. The highest etch selectivity of SiO2 and Si3N4 over poly-Si was achieved with HFE-347mmy as high as 103 for SiO2 to poly-Si and 189 for Si3N4 to poly-Si. This study demonstrates that C4H3F7O isomers can help reduce global warming by replacing the conventional perfluorocarbons and achieving high selectivity of SiO2 to poly-Si and Si3N4 to poly-Si.
Keywords: Ar plasmas; Atomic layer etching; Carbon rich; Chemical sputtering; Etch selectivity; Fluorinated surface; Global warming potential; Low-GWP; Methyl ethers; Plasma atomic layer etching; etch selectivity; low-GWP; plasma atomic layer etching; silicon nitride; silicon oxide